2015
DOI: 10.22158/selt.v3n1p28
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing Microteaching at Sultan Qaboos University

Abstract: <p><em>This study was an attempt to maximize the effectiveness of microteaching at </em><em>SQU</em><em>. It proposed a model incorporating five components: (1) planning and feedback, (2) teaching and observation, (3) self-assessment and reflection, (4) peers’ feedback, and (5) tutor’s feedback. The model was applied to a group of 24 student-teachers of English attending the microteaching course at the College of Education, Sultan Qaboos University. To measure the effectiven… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 17 publications
1
6
0
Order By: Relevance
“…In the statements of the student teachers, microteaching practices were admitted to be supportive for discovering and analysing their strengths and weaknesses as prospective teachers. The results of the present study support the prior literature pointing out that microteaching applications are practical experiences for producing desired change in the objectives of training teachers (Ghanagura, Nair, & Young, 2013;Ping, 2013) and for offering student teachers opportunities to orient themselves to teaching issues (Al-Humaidi & Abu-Rahmah, 2015;Eick et al, 2005). Among the findings of the present study, the student teachers' desire to receive feedback after microteaching sessions for developing teaching skills and capabilities is another point supporting the findings of the previous studies (Kaustuva et al, 2015;Marzano, 2003;Umeh et al, 2015).…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…In the statements of the student teachers, microteaching practices were admitted to be supportive for discovering and analysing their strengths and weaknesses as prospective teachers. The results of the present study support the prior literature pointing out that microteaching applications are practical experiences for producing desired change in the objectives of training teachers (Ghanagura, Nair, & Young, 2013;Ping, 2013) and for offering student teachers opportunities to orient themselves to teaching issues (Al-Humaidi & Abu-Rahmah, 2015;Eick et al, 2005). Among the findings of the present study, the student teachers' desire to receive feedback after microteaching sessions for developing teaching skills and capabilities is another point supporting the findings of the previous studies (Kaustuva et al, 2015;Marzano, 2003;Umeh et al, 2015).…”
Section: Discussionsupporting
confidence: 87%
“…The use of video with guided reflection is important for assisting student teachers to form links between theory and practice and for raising awareness of teaching practices (Kourieos, 2016). Student teachers can benefit from a video-tape recording on microteaching for self-evaluation and self-analysis (Honigsfeld & Schiering, 2004), immediate peer and tutor feedback (Al-Humaidi & Abu-Rahmah, 2015;McAlpine & Weston, 2002;Umeh et al, 2015), and reflective practice (Kane, Sandretto, & Heath, 2002;Kponja, 2001). Receiving feedback on a microteaching task fosters student teachers' teaching skills development (Bransford, Brown, & Cocking, 2000;Fernandez & Robinson, 2006;Marzano, 2003;Ndileleni & Maphosa, 2014;Subramaniam, 2006).…”
Section: Microteaching Practices and Evaluationmentioning
confidence: 99%
“…In conclusion, microteaching can be regarded as an effective practice in pre-service teacher education as it offers an atmosphere of gaining experience (Göçer, 2015), promoting selfreflection (Kavanoz & Yüksel, 2010), professional development (Elghotmy, 2012;He & Yan, 2011;Savaş, 2012) and the development of teaching practice (Al-Humaidi & Abu-Rahman, 2015;Coşkun, 2016;Ping, 2013). Therefore, the combination of all these factors inevitably enhances the sense of professional self-efficacy of pre-service EFL teachers.…”
Section: Discussionmentioning
confidence: 99%
“…This study reported a microteaching model applied in an English language teacher training institution in Yogyakarta, Indonesia. Although prior studies had been conducted to investigate the effectiveness and benefits of microteaching (Ismail, 2011;Al-Humaidi & Abu-Rahmah, 2015;Arsal, 2015), the present study shed new light on the practices of microteaching as it explored more deeply on the preservice teachers' first experiences in performing microteaching and how their first experienced improved their critical thinking skills. Different from the microteaching model applied in the three prior studies which was an individual task, that of the present study was conducted in groups.…”
Section: A Introductionmentioning
confidence: 98%
“…Prior studies have reported the benefits microteaching offers. Al-Humaidi and Abu-Rahmah (2015) conducted an experimental study to 24 Omani student-teachers to explore the effectiveness of a proposed model of microteaching applied in Sultan Qaboos University. Using a checklist as the instrument of the study, the participants were asked to assess their peers' teaching performance in the microteaching.…”
Section: A Introductionmentioning
confidence: 99%